Characteristics of and Virulence Factors Associated with Biofilm Formation in Clinical Enterococcus faecalis Isolates in China - Zheng, Jin-Xin; Wu, Yang; Lin, Zhi-Wei; Pu, Zhang-Ya; Yao, Wei-Ming; Chen, Zhong; Li, Duo-Yun; Deng, Qi-Wen; Qu, Di; Yu, Zhi-Jian (Frontiers in Microbiology, 2017)
Enterococcus faecalis biofilm traits and distribution characteristics in China have not been clarified. This study aimed to determine the prevalence and characteristics of E. faecalis biofilm formation in a sample of clinical isolates and to explore the virulence factors associated with biofilm formation in those isolates. A total of 265 E. faecalis isolates were collected from patients in Shenzhen, China. Virulence genes were detected within the genomes of the microbes by polymerase chain reaction (PCR). The isolates were subjected to multilocus sequence typing (MLST) based on housekeeping genes. Biofilms were detected by crystal violet staining. The expression levels of the clinical E. faecalis isolates’ genes were determined by quantitative real-time polymerase chain reaction. The prevalence of biofilm formation among E. faecalis clinical isolates was 47.2%. MLST yielded 44 different sequence types (STs). The main STs were ST16 and ST179; the ST16 isolates were more likely to form strong or medium biofilm than the ST179 isolates (p < 0.001). Strong or medium biofilm formation was more common in linezolid-resistant isolates than in linezolid-sensitive isolates (p = 0.001). Biofilm formation was more frequently detected in enterococcal surface protein (esp+), surface aggregating protein (asa1+), cytolysin A (cylA+), or aggregation substance (agg+) positive isolates than in isolates that were negative (−) for these virulence factors. Multivariate regression analysis indicated that cylA [odds ratio (OR) 4.083, p < 0.001] was a risk factor for weak biofilm formation, and that esp (OR 8.207, p < 0.001) was a risk factor for strong or medium biofilm formation. The expression of cylA was raised (4.02 to 6.00-fold) in weak biofilm isolates compared to the biofilm-negative isolates, and the expression of esp was greatly elevated (11.39 to 134.08-fold) in strong biofilm isolates compared to biofilm-negative isolates. In conclusion, the ST16 classification and linezolid resistance were positively associated with strong/medium biofilm formation in clinical E. faecalis isolates. cylA was associated with weak biofilm formation, and esp was only associated with strong or medium biofilm formation of the clinical E. faecalis isolates.